Performance analysis of packets scheduling with preemptive / Norjanah Kastaman - Kastaman, Norjanah (2008)
In today's high-speed packet networks that support various applications with different service requirements, congestion control is an important issue. One of the methods for preventing congestion is packet scheduling [10]. Packet scheduling in network can provide guaranteed performance in terms of delay, delay jitter, packet loss, overflow and throughput. The main objective of this thesis is to implement a model for the packet scheduling mechanism, perform a simulation based performance analysis, and compare it to three commonly used scheduling mechanisms: WFQ, Custom Queuing, and Priority Queuing. We implement a scheduler model and incorporate it into the IP layer output queues using OPNET 10.5 simulation tool. We measure the performance of the algorithms in terms of delay time, size of packet and overflow from different traffic flows during various time periods. We also simulate a network running several Internet applications: VoIP, FTP, video conferencing and we observe the impact of scheduling algorithms on the performance of these applications. Our simulation results indicate comparison of Priority Queuing, WFQ and Custom Queuing in internet application in terms of delay time, size of packet and overflow.